Komparasi Keaktifan Dan Hasil Belajar Akuntansi Pengendalian Biaya Antara Lulusan SMK Dengan SMA Pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Tahun Angkatan 2013/2014 - Ranti, Tri Dewa; , Drs. Muhammad Yahya, M.Si (2016)
The aims of this study are to know: 1) Whether learning of vocational high school graduation is better than senior high school graduation on expense control accountancy subject for accountancy students of 2013/ 2014 generation of FKIP UMS. 2) Whether learning outcome of vocational high school graduation is better than senior high school graduation on expense control accountancy subject for accountancy students of 2013/ 2014 generation of FKIP UMS. 3) Whether there is a difference of learning active and learning outcome between vocational high school graduation and senior high school graduation for accountancy students of 2013/ 2014 generation of FKIP UMS. The type of this study is a comparative quantitative research. Sample of this research are 110 students that are taken by technique of simple random sampling type. Techniques of collecting data that used are documentation for value of expense control accountancy and questionnaire for value of learning active. Based on the data analysis of learning active, it found thitung = 3,106 > ttabel =2,273 that means there is a difference of learning active on expense control accountancy subject for students of accountancy department 2013/ 2014 year generation FKIP UMS. The average of learning active value for vocational high school graduation is 53, 57 whereas the average of learning active value for senior high school graduation is 49, 51. It means that vocational high school graduation is better than senior high school graduation in learning active of expense control accountancy subject. Based on the data analysis of learning outcome, it found thitung =3,730 > ttabel =2,273 that means there is a difference of learning outcome on expense control accountancy subject for students of accountancy department 2013/ 2014 year generation FKIP UMS. The average of learning outcome value for vocational high school graduation is 71,768 the average of learning outcome value for senior high school graduation is 64, 381. It means that vocational high school graduation is better than senior high school graduation in learning outcome of expense control accountancy subject. Both learning active and learning outcome shows that thitung > ttabel. Learning active thitung > ttabel is 3,730>2,273, taken from the average of learning active and learning outcome of vocational high school graduation and senior high school graduation. It means that learning active and learning outcome of academic student is better than learning active and learning outcome of vocational high school graduation and senior high school graduation. Both learning active and learning outcome has a similar value nilai thitung > ttabel so H0 is refused that means there is a difference between learning active and learning outcome on expense control accountancy subject for academic students who had graduated from vocational high school and academic students who had graduated from senior high school.